PENGARUH RELAKSASI NAFAS DALAM TERHADAP SKALA NYERI KEPALA PADA PASIEN HIPERTENSI DI WILAYAH KERJA PUSKESMAS SAWAH LEBAR KOTA BENGKULU - Fernalia Fernalia; Wiwik Priyanti; S. Effendi; Dita Amita (Universitas Malahayati Lampung, 2019)
ABSTRACT: EFFECT OF DEEP BREATHING RELAXATION TO HEADACHE PAIN LEVEL AMONG HYPERTENSION PATIENTS IN AREA OF SAWAH LEBAR PRIMARY HEALTH CARE BENGKULU CITY Backround: Headache is a problem that is often felt by people with hypertension. Deep breath relaxation is a form of nursing care which in this case the nurse teaches clients how to do deep breathing besides being able to reduce pain intensity, it can also increase lung ventilation and improve blood oxygenation.Purpose: The purpose of this study was to determine the Effect of Deep Breathing Relaxation to Headache Pain Level on Hypertension Patients in Area of Sawah Lebar Primary Health Care Bengkulu City.Methods: This study used pre experiment with one group pretest-posttest design. Population in this study were all hypertension patients who ever treated in Area of Sawah Lebar Primary Health Care Bengkulu City in 2017 with the amount of 584 patients. Sampling technique used accidental sampling obtained 41 respondents. Collecting data in this study used primary data with measured pain intensity with objective before and after Deep Breathing Relaxation used observation instrument with pain level numeric rating scale (NRS). Data analysis used Wilcoxon sign rank test.Result: The result of this study showed from 41 respondents obtained average pain level before Deep Breathing Relaxation were 4,37 for moderate pain 41 and standard deviation 0,581. While average pain level after Deep Breathing Relaxation were 3,02 for mild pain (36), moderate pain (5) and standard deviation 0,570. From statistic test obtained p=0,000 0,05 means H0 rejected and Ha accepted. Both variable had difference headache pain level after Deep Breathing Relaxation.Conclusion: Conclusion is there is effect of Deep Breathing Relaxation to Headache Pain Level on Hypertension Patients in Area of Sawah Lebar Primary Health Care Bengkulu City. Keywords: Deep Breathing Relaxation, Headache Pain Level, Hypertension